Tinjauan Literatur: Analisis Sintesis dan Efektivitas Senyawa Kalkon serta Turunannya sebagai Agen Antibakteri - Damara , Dandy Satria; Akifah , Muthia Nur; Putri , Indah Syah; Utami , Marsah Rahmawati (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Chalcones are flavonoid compounds that have attracted attention in the development of antibacterial agents. This literature review aims to examine the synthesis and effectiveness of chalcone compounds and their derivatives as antibacterials. Through descriptive analysis, chalcone synthesis was carried out using several methods, one of which was the condensation between benzaldehyde and acetophenone, followed by structural modification to produce various chalcone derivatives. The antibacterial activity of chalcone compounds and their derivatives was tested against bacteria such as S. aureus, E. coli, B. substillis, and other types of bacteria. The results of the review of several literatures obtained online through Google, Google Scholar, and Publish or Perish were carried out using the keywords